Exploring Topic Card in Collaborative Descriptive Speaking Activities among Junior High School EFL Classroom - Semaria Girsang; Alfiah Zahraini Silalahi; Ridwin Purba; Anita Purna; Rita Mahriza (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
This study explored the use of topic cards in collaborative descriptive speaking activities among junior high school EFL learners. Although collaborative speaking activities have been widely discussed in EFL learning, few studies have specially examined to the integration of topic cards as scaffolding support in descriptive speaking interaction at the junior high school level. This study employed a quantitative approach using a pre-test and post-test control group design involving 62 eight-grade students at UPTD SMP Negeri 1 Pematangsiantar. The experimental class participated in collaborative speaking activities using topic card, while the control class received conventional speaking instruction. The data were collected through speaking test assessing pronunciation, grammar, vocabulary, and fluency and were analyzed using SPSS version 27.0. The findings reveled that both groups demonstrated improvement after the instructional process. However, the independent samples t-test indicated that the statistical analysis did not indicate a significance, students in the experimental class demonstrated greater classroom participation, interaction, and confidence during speaking activities. These findings suggest that topic cards may function as scaffolding support for collaborative speaking interaction in EFL classrooms.